New design wind speed for a wind turbine generator (WTG) considering typhoon loads - Garciano, Lessandro Estelito O. (Animo Repository, 2022)
Strong typhoons in Asian countries occur frequently. Therefore if WTGs are constructed in these areas these extreme loads should be taken into account. In view of this, we analyzed the probability of buckling failure (pf) of a WTG considering extreme wind speeds distributions from both typhoon and non-typhoon prone areas and the buckling resistance of a tower in terms of wind speeds. Since the pf decreases when typhoons are considered we introduced a new buckling resistance against this load. This assertion maintains the original pf between the original buckling resistance and the non-typhoon load distribution. Based on this new wind speed resistance a new 50-year design wind speed (V e50new) and a new reference wind speed (V refnew) is obtained. Some numerical simulation were done to illustrate the proposed concept using typhoon data from 50 weather stations in the Philippines. For a specific diameter and thickness of the tower V e50new was calculated. Using kriging method of of ArcGIS geostatistical analyst the results were interpolated to other unmeasured areas to create a prediction surface for V e50new. The results are useful for wind farm owners.